Interdisciplinary Approaches to Multilingualism - Rahat Naqvi (Frontiers Research Topics, 2015)
This research topic stems from the "Interdisciplinary Approaches to Multilingualism" conference, which was hosted by the Language Research Centre at the University of Calgary. It was the first conference of its kind, which brought together the work of researchers, educators, and policy makers in the areas of first and second language acquisition from psycholinguistic and pedagogical perspectives. The goal was to provide an opportunity for participants to engage with the implications of multilingualism from a range of perspectives, including the effects of being bilingual from infancy to adulthood, the process and benefits of learning multiple languages, and the impact of multilingualism on society.